Parlamentarne platformy oddziaływania na realziację zadań rządu związkowego w Republice Federalnej Niemiec: [Parlamentary platforms of influencing the realization of the tasks of the government of the Union in Federal Republic of Germany] (Studia Prawnicze / The Legal Studies, 2023)
The paper provides an analysis of the influence of the parliamentary institutions on the working and activity of the government in the Federal Republic of Germany. The author does not aim at presenting the parliamentary institutions as such: in their constitutional position, authority exercised in the political system of the state, and the mechanism of their working. He concentrates on particular aspects of their formal and real functions: on their role as platforms of legally organised political influence on the activity of the federal government. In the first part of his paper, he presents the competence and activity of the federal council — Bundesrat — in legislation, and supervision of regulations issued by federal government, to direct the execution of federal. tasks. In the second part, he tries to analyse the mechanism of political parliamentary influence exercised by federal house of representatives Bundestag — on the exercise of its functions by the federal government.According to the author federal council is a second chamber of federal parliament, although organised in a very particular form. It assures the governing strata of several partial states — Länder — a functional platform of influence on activity of federal administration. The legal basis of this influence is provided by the authority of the federal council to give necessary assent to ca 50% of federal legislation and ca 75% of administrative regulations issued by federal government to state authorities. As practical effect of its authority a system of informal cooperation between federal and state administration was created. It provides not only channels of communication, but a structure of influencing the government in its activity on behalf of power-elites centred in the government of several states. The author tries to treat the subject of relations between the representative chamber and the parliamentary government in GFR in most realistic way. He accepts as dominant the position of federal government in the political system of the GFR. This does not contradict the legally superior authority of the representative chamber, and its real capacity, to exercise a controlling activity, in respect of legislation and in allowance of funds necessary to effect the state tasks. The author presents the structure of activities of the representative chamber and of the parliamentary parties providing formal and informal means to assure the possibilities to take i consideration, supervise and influence the activity of federal government.